Attributing Mind to Groups and Their Members on Two Dimensions - Tanibe, Tetsushi; Hashimoto, Takaaki; Tomabechi, Tobu; Masamoto, Taku; Karasawa, Kaori (Frontiers in Psychology, 2019)
Psychological research has revealed that people attribute mental states to groups such as companies, especially to those groups that are highly entitative. Moreover, attributing a mind to a group results in the decreased attribution of mind to individual group members. Recent research has demonstrated that the minds of others are perceived in two dimensions—agency and experience. The present study investigated the possibility that this two-dimensional structure exists in mind attribution to groups, and group entitativity has different patterns of relations with these dimensions. A vignette experiment revealed that highly entitative groups were attributed both agency and experience to greater degrees compared to non-entitative groups, while group entitativity reduced only the attribution of agency to the individual group members. Individual members were attributed an equivalent amount of experience regardless of group entitativity. Mind attribution to individual members showed an unpredicted third factor of other-recognition, which was positively related to group entitativity. The implications of mind attribution to moral issues were discussed.